2007
DOI: 10.3310/hta11390
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and economic model of the clinical effectiveness and cost-effectiveness of interventions for preventing relapse in people with bipolar disorder

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 85 publications
(225 reference statements)
0
76
0
6
Order By: Relevance
“…However, three recent meta-analyses of LTG trials found an overall positive effect, though this wasn't observable on a per study basis Smith et al, 2007;Soares-Weiser et al, 2007). Four double-blind studies assessing LTG for the treatment of BDII have been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, three recent meta-analyses of LTG trials found an overall positive effect, though this wasn't observable on a per study basis Smith et al, 2007;Soares-Weiser et al, 2007). Four double-blind studies assessing LTG for the treatment of BDII have been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…2003 yılında yapılan çalışmanın örneklemini oluşturan 120 hastanın %31'i (37 hasta), DSM-IV kişilik bozukluğu ölçütlerine sahip olduğundan, bu araştırmanın örneklemini oluş-turmuştur. Çalışmada yer alan katılımcıların yaş ortalaması deney grubunda 36 olarak belirlenmiştir. Grupların daha önce yaşadıkları ortalama relaps sayısı deney grubunda 10.18±9.34, kontrol grubunda 9.52±7.19 olarak bulunmuştur.…”
Section: öRneklemunclassified
“…Bipolar bozuklukta relaps önleme-ye yönelik yapılan psikoeğitimlerin değerlendirildiği meta analiz çalışmalarından elde edilen bulgular da psikoeğitim gibi tamamlayıcı psikoterapi yöntemlerinin relapsları önlemede etkili olduğunu ortaya koymaktadı. [17,[34][35][36] Bipolar bozuklukta relapsların tekrarlaması, özkıyım riski, relapslar nedeniyle ortaya çıkacak psikososyal sonuçlar ve hastalığa eşlik eden bozukluklar (alkol ve madde kullanım bozuklukları) nedeniyle koruyucu tedavinin gerekliliği tartışılmaz bir durumdur. [37,38] Bu görüşü destekler nitelikte incelenen çalışmaların tamamında uygulanan psikoeğitimin, yaşanan relaps sayılarını azalttığı görülmüştür.…”
Section: Sosyal İşlevsellikunclassified
“…Em pacientes com quadro de bipolaridade com predominância depressiva, o melhor tratamento farmacológico verificado -combinado com TCC -tem sido por meio do uso de Valproato, Lítio e Lítio combinado com Imipramina. Em pacientes cuja predominância do transtorno está na fase maníaca, o melhor tratamento tem sido o uso de Olanzapina e TCC (Soares-Weiser et al, 2007).…”
Section: Transtorno De Humor Bipolarunclassified